Compositions and Co-occurrence Patterns of Bacterial Communities Associated With Polymer- and ASP-Flooded Petroleum Reservoir Blocks - Ren, Guoling; Wang, Jinlong; Qu, Lina; Li, Wei; Hu, Min; Bian, Lihong; Zhang, Yiting; Le, Jianjun; Dou, Xumou; Chen, Xinhong; Bai, Lulu; Li, Yue (Frontiers in Microbiology, 2020)
With growing global energy demand and depleting reserves, enhanced oil recovery (EOR) from existing brown fields becomes more and more important. Polymer flooding (PF) technology and alkaline-surfactant-polymer (ASP) flooding technology have been widely used in Daqing Oilfield. However, how to further improve oil recovery after chemical flooding reserviors is a very difficult problem. Microbial enhanced oil recovery technology is a promising alternative technology. But the bacterial communities in polymer flooding and ASP flooding oil reservoirs have rarely been investigated. We investigated the bacterial communities in ASP flooding wells and in polymer flooding wells by 16S rRNA gene sequencing. Bacterial community composition differed significantly between polymer flooding and ASP flooding wells. Proteobacteria (33.75%), Epsilonbacteraeota (27.28%), Synergistetes (11.90%) and Firmicutes (11.38%) were dominate in the polymer blooding wells, and Proteobacteria accounted for 63.05% of the bacterial communities inhabiting the ASP flooding wells. Co-occurrence network analysis revealed non-random assembly patterns of bacterial composition in ASP flooding and polymer flooding wells, ASP flooding decreased bacterial network complexity, suggesting that the application of ASP reduced the tightened of bacterial interactions.